MODEL PEMBELAJARAN MASTER DALAM KEMAMPUAN MEMPRESENTASIKAN TEKS RESENSI NOVEL BERBANTUAN INSTAGRAM - Lutfi Syauki Faznur; Wika Soviana Devi; Bunga Tisya Marwa (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2022)
The background of the writing is the lack of students' ability in speaking skills. In addition, the application of learning models and learning media that are less than optimal in developing materials for presenting novel review texts. The purpose of this study was to determine the effect of the MASTER learning model on the ability to present review texts assisted by Instagram, and student learning outcomes. This research was conducted at SMAN 47 Jakarta, in class XI MIPA 3 and XI MIPA 4. The research method used in this study was True Experiment with Posttest Only Control Design. The results showed that there was an effect of the MASTER learning model with the help of Instagram on the ability to present review texts. This is based on the results of the Independent Sample Test hypothesis, there are sig 0.000 ˂0.05 and a Thit value of 7.627 Ttab 1.998. Therefore, Ha is accepted and H0 is rejected, meaning that there is an effect of the MASTER learning model on the ability to present novel review texts with the help of Instagram. Keywords: master model; novel review; instagram